Utilization Review of Imaging Equipment: An insight into CT Scanning (Medico Legal Update, 2021)
Introduction: Radio diagnosis service plays a crucial role in diagnosis of the patient’s disease. The volumeof patients utilising this service is very high. This service also takes away the sizeable share of total capitalinvestment and therefore, the optimal utilization of this service becomes important.Methodology: Literature review was done through Google scholar, electronic database of PubMed andother relevant databases. The query terms like Utilization Review of Imaging Equipment, Utilisation of CTScanners, Capacity of Scanners in Radiology and Waiting Times for Imaging were used to fetch the relevantdata sources. Around 130 articles were reviewed and analysed.Results: The number of CT Scans per 1 million of population in High Income (HI), Upper Middle Income(UMI), Lower Middle Income (LMI) are 14.7, 7.3, 3.7. The CT scanners are one of the most expensivepieces of medical equipment in hospitals, with CT scanners costing between $1 million (?7 crore) and $2million (?14 crore).There is a substantial variation in the utilisation of these services, including number of scans per day andwait times. Increasing the scanner efficiency and utilisationcan significantly decrease the cost per scan andincrease access to imaging services.Expanding capacity, improving operating procedures by reducing change-over times, and improvingcapacity allocation in combination with scheduling procedures can contribute to the overall reduction of CTaccess time.Discussion and Conclusion: By acquiring Utilization data about CT Scanners, we get to know a completeand accurate overview of how Scanners are used. The CT scanner utilisation can be improved in both publicand private health sector by analysingthe key information about the utilisation of their own and other healthservices’ CT scanners.